INFLUENCE OF NITRATE ON SULFIDOGENIC ACTIVITY OF BACTERIA DESULFOMICROBIUM SP. CRR3 - Л. С. Дорош; Т. Б. Перетятко; С. П. Гудзь (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
The aim of this work was to study influence of nitrate on the effectivity of sulphate reduction and accumulation of hydrogen sulfide by bacteria Desulfomicrobium sp. CrR3. Methods. The object of the study was chromiumresistant sulphate-reducing bacteria Desulfomicrobium sp. CrR3. Effect of nitrate on sulfidogenic activity of bacteria was determined by the change of biomass and concentration of sulfates, nitrate and hydrogen sulfide in culture medium. Results. It was established the influence of nitrate ions on sulfidogenic activity of bacteria Desulfomicrobium sp.CrR3. 5 mM nitrate in adding culture medium caused the inhibition of sulphate reduction by 40 %. With the increase of nitrate concentrations up to 10 mM the inhibition of sulfate reduction was completely. Conclusions. The results indicate that the addition of nitrate caused the inhibition of the dissimilatory sulfate reduction by bacteriaDesulfomicrobium sp. CrR3.